1976
DOI: 10.1038/sc.1976.25
|View full text |Cite
|
Sign up to set email alerts
|

Disodium etidronate in the prevention of heterotopic ossification following spinal cord injury (preliminary report)

Abstract: Heterotopic ossification is a frequent complication following spinal cord injury with 16 per cent to 53 per cent of patients developing varying degrees of pathologic ossification. The diphosphonates are known to block the transformation of amorphous calcium phosphate into crystalline hydroxyapatite. Therefore, one of the diphosphonates, disodium etidronate (generic name of disodium ethane-1-hydroxy-1, 1-diphosphonate (EHDP) was selected fro clinical trials to study the effectiveness of EHDP in preventing heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 11 publications
0
27
1
2
Order By: Relevance
“…172 ± 175 However, operative resection of NHO has been associated with severe complications and poor outcome. 171 These complications include deep (2 ± 5%) 174,175 or super®cial infection (7 ± 38%), 45,49,174,175 post-operative haemorrhage (5 ± 38%), 45,173 and excessive intra-operative bleeding requiring (multiple) blood transfusions (9 ± 83%). 49,174 ± 176 Moreover, intra-and post-operative fracturation of bone may occur in the case of severe osteoporosis.…”
Section: Surgical Resectionmentioning
confidence: 99%
See 2 more Smart Citations
“…172 ± 175 However, operative resection of NHO has been associated with severe complications and poor outcome. 171 These complications include deep (2 ± 5%) 174,175 or super®cial infection (7 ± 38%), 45,49,174,175 post-operative haemorrhage (5 ± 38%), 45,173 and excessive intra-operative bleeding requiring (multiple) blood transfusions (9 ± 83%). 49,174 ± 176 Moreover, intra-and post-operative fracturation of bone may occur in the case of severe osteoporosis.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…The post-operative recurrence of NHO depends on the de®nition used and the followup period. Radiographic signs of NHO recurrence have been mentioned in 82 ± 100% of the operated SCI patients, 45,49,173,174 although clinically signi®cant NHO would develop in only 17 ± 58% of the cases. 10,45,49,173,174,176 It has been suggested that the recurrence after resection can be reduced if NHO is removed only once the ®rst and second phase of the bone scan have normalized.…”
Section: Surgical Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevention of HO with etidronate after SCI had an e ect mainly on the reduction of progression of ectopic bone than on the incidence of this complication. 18,19 The e ect of NSAIDs on the prevention of HO following total hip arthroplasty (THA) is well accepted. 20,21 In only a few patients with SCI these drugs have been used as a`secondary' prevention after surgical removal of HO.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,20,21 In the present study we report an e ective management of HO which was based on the screening of asymptomatic patients by bone scintigraphy, consequently resulting in considerable better prevention of HO than reported in previous studies where the diagnosis of HO was based on the radiographic examination. 17,19 …”
Section: Introductionmentioning
confidence: 99%